Newfoundland - Edward Stanford Ltd. ([London], 1895)
Colour. Prime meridian Greenwich. Relief shown by hachures and spot heights. Bar scale in English miles. Shows telegraph lines, cables and railways. Shows the island of Newfoundland and southern Labrador only. CNS map no. 403.